Avaliação dos aspectos microbiológicos do caldo de diferentes variedades e partes do colmo da cana-de-açúcar sob manejo orgânico - Martini, Cristina (Universidade Federal de São Carlos, 2009)
For the artisanal cachaça production, which is a beverage obtained after distillation of the fermented sugar cane juice, natural starter ferment ( caipira ferment) is utilized, in which crushed corn, rice bran and citric fruit juice are added to sugar cane juice. The primary source of microorganisms, yeasts especially, is the sugar cane juice itself, and although the cachaça sensorial quality is recognized when this ferment is utilized, there are some inconvenients as difficulties in the quality control due to the high level of contaminants and extensive preparation periods. In this context, this work aimed the evaluation of microbiological (yeast numbers) and physico-chemical aspects of the juice extracted from 10 sugar cane varieties, in three harvesting periods (May, September and December) in an area under organic management. The same analysis were performed for the juice extracted from different stalk sections (lower, medium and upper section) from three sugar cane varieties (RB72454, RB835486 e RB867515) under organic management, seeking for information which could contribute to the variety management allowing a faster and efficient natural ferment preparation. A significant decrease in the yeast numbers (CFU/mL) in the juice were observed when the maximum point of maturation was reached for the majority of the varieties. However, the proportion (%) of Saccharomyces increased with the sugar cane maturation, in such a way that early and medium maturation varieties (RB835054, RB835486, RB845210 and RB855156) may be utilized at the beginning of the harvest period (in May) for the natural ferment preparation, which could result in diminished preparation time and faster fermentation. Among the early maturation varieties, RB845210 is indicated because it also presented high reducing sugar and protein in the juice. Regarding the juice extracted from different stalk sections, the upper section (from 11th to 15th internode, without the palmito ) could be indicated for the natural ferment preparation because of higher yeast numbers, higher reducing sugar concentration and acidity, which promote the yeast growth. It was verified that Saccharomyces yeasts show a transient and spatial distribution along with sugar concentration gradient. The knowledge of this behavior and variety characteristics can ease the variety management aiming the production and performance of the natural starter ferment, in order to contribute for the organic cachaça production.
Microbiological evaluation of the juice from different varieties and stalk sections of sugar cane cultivated under organic management
Keywords: Agroecologia; Levedos; Fermentação; Cana-deaçucar; Garapa; Manejo orgânico; CIENCIAS AGRARIAS